Microgel suspensions : fundamentals and applications - Fernandez-Nieves, Alberto ;Wyss, Hans ;Mattsson, Johan ;Weitz, David A. (Weinheim : Wiley-Vch Verlag and Company KGaA, 2011)
Providing a vital link between chemistry and physics on the nanoscale, this book offers concise coverage of the entire topic in five major sections, beginning with synthesis of microgel particles and continuing with their physical properties. The phase behavior and dynamics of resulting microgel suspensions feature in the third section, followed by their mechanical properties. It concludes with detailed accounts of numerous industrial, commercial and medical applications. Edited by David Weitz, Professor at Harvard and one of the world's pre-eminent experts in the field.
Front Matter -- Synthesis. Microgels and Their Synthesis: An Introduction / Robert Pelton, Todd Hoare -- Polymerization Kinetics of Microgel Particles / Abdelhamid Elaissari, Ali Reza Mahdavian -- New Functional Microgels from Microfluidics / Jin-Woong Kim, Liang-Yin Chu -- Physical Properties of Microgel Particles. Swelling Thermodynamics of Microgel Particles / Benjamin Sierra-Martin, Juan Jose Lietor-Santos, Antonio Fernandez-Barbero, Toan T Nguyen, Alberto Fernandez-Nieves -- Determination of Microgel Structure by Small-Angle Neutron Scattering / Walter Richtering, Ingo Berndt, Jan Skov Pedersen -- Interactions and Colloid Stability of Microgel Particles / Brian Vincent, Brian Saunders -- Phase Behavior and Dynamics of Microgel Suspensions. Structure and Thermodynamics of Ionic Microgels / Christos N Likos -- Elasticity of Soft Particles and Colloids near the Jamming Threshold / Matthieu Wyart -- Crystallization of Microgel Spheres / Zhibing Hu -- Melting and Geometric Frustration in Temperature-Sensitive Colloids / Ahmed M Alsayed, Yilong Han, Arjun G Yodh -- Mechanical Properties. Yielding, Flow, and Slip in Microgel Suspensions: From Microstructure to Macroscopic Rheology / Michel Cloitre -- Mechanics of Single Microgel Particles / Hans M Wyss, Johan Mattsson, Thomas Franke, Alberto Fernandez-Nieves, David A Weitz -- Rheology of Industrially Relevant Microgels / Jason R Stokes -- Applications. Exploiting the Optical Properties of Microgels and Hydrogels as Microlenses and Photonic Crystals in Sensing Applications / L Andrew Lyon, Grant R Hendrickson, Zhiyong Meng, Ashlee N St John Iyer -- Microgels in Drug Delivery / Martin Malmsten -- Microgels for Oil Recovery / Yuxing Ben, Ian Robb, Peng Tonmukayakul, Qiang Wang -- Applications of Biopolymer Microgels / Eugene Pashkovski -- Index.
Includes bibliographical references and index.
Keywords: SUSPENSION (CHEMISTRY)